Semi-quantitative model of the gating of KcsA ion channel. 2. Dynamic self-organization model of the gating - Kharkyanen, V.N.; Yesylevskyy, S.O.; Berezetskaya, N.M.; Boiteux, C.; Ramseyer, Ch. (Вiopolymers and Cell, 2009)
The aim of this series of papers is to develop the semi-quantitative theory of the gating of KcsA channel. Methods. For this purpose available structural and electrophysiological data and the results of molecular dynamics simulations were used in the context of the concept of dynamical self-organization. In the second paper we describe the principles of dynamic self-organization and develop the theory of KcsA channel gating based on this concept. Conclusions. Present work is the first successful attempt of combining the structure and dynamics of real protein and the general concept of dynamic self-organization. Мета даної серії робіт полягає у розробці напівкількісної теорії воротних процесів в іонному каналі KcsA. Методи. Для цього залучено доступні експериментальні дані, а також результати молекулярної динаміки у контексті концепції динамічної самоорганізації. Результати. У другій роботі серії описано принципи динамічної самоорганізації та розроблено теорію воротних процесів у каналі KcsA, що базується на цих принципах. Наведено першу успішну спробу об’єднання даних щодо структури та динаміки реального білка з концепцією динамічної самоорганізації. Целью данной серии работ является разработка полуколичественной теории воротных процессов в ионном канале KcsA. Методы. Для этого использованы доступные экспериментальные данные, а также результаты молекулярной динамики в контексте концепции динамической самоорганизации. Результаты. Во второй работе серии описаны принципы динамической самоорганизации и разработана теория воротных процессов в канале KcsA, базирующаяся на этих принципах. Представлена первая успешная попытка объединения данных о структуре и динамике реального белка с концепцией динамической самоорганизации.